The activities of teaching Arabic speaking skills among debate coaches [Aktiviti pengajaran kemahiran bertutur bahasa Arab dalam kalangan jurulatih debat] - Samah R.; Abdul Hamid M.F.; Hafes Sha'ari S.; Helmi Mohamad A. (2024)
Arabic debaters in national secondary school are students who not only possess excellent command of the language but are also able to articulate effectively their thoughts and argument in the Arabic language. The training sessions prepare the debaters with effective oral skills that are individually tailored to suit every debater's needs. The aim of this study is to identify the activities involved in the training sessions that have been designed by the coaches, particularly based on the approaches of gathering relevant vocabulary and word collocation, reinforcement and application. The data was collected by using questionnaires that focused on the three approaches. The respondents were 34 debate coaches from selected Sekolah Menengah Kebangsaan Agama, Sekolah Agama Bantuan Kerajaan and Kelas Aliran Agama. Findings from the study indicate that the debate coaches always implemented the three approaches in their training sessions. In the approach of gathering relevant Arabic words and sentences, the activity with the highest mean is finding the meaning of new words in Arabic through Arab-Malay dictionary. In the approach of reinforcement, the activity with the highest mean is correcting language errors made by students. In the approach of application, the activity with the highest mean is to make students translate sentences or words and make short sentences. This study proposes for the implementation of the three approaches in the teaching and learning of Arabic language in secondary schools, in order to enhance the debaters' oral proficiency skills of the target language.